Malmquist theorem for solutions of differential equations in a neighborhood of a logarithmic singular point - Mokhonko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
The Malmquist theorem (1913) on the growth of meromorphic solutions of the differential equation f ′ = P(z,f) / Q(z,f), where P(z,f) and Q(z,f) are polynomials in all variables, is proved for the case of meromorphic solutions with logarithmic singularity at infinity.